(untitled) (Rheumatology Reports, 2011)
Light chain deposition disease associated with primary Sjogren’s syndrome has been rarely reported in the medical literature. We report a 65-year old Caucasian woman with Sjogren’s syndrome (SS) for twenty eight years associated with nodular pulmonary light chain deposition disease. This case is unique in the improvement of clinical symptoms and pulmonary function tests following treatment with mycophenolate mofetil (MMF). Primary SS is an automimmune exocrinopathy which is characterized by keratoconjunctivitis sicca and xerostomia. SS is known to be associated with B cell hyperactivity, polyclonal gammopathy and low grade marginal zone B cell lymphoma. Light chain deposition disease is a non-amyloid monoclonal immunoglobulin disorder that is caused by a clonal plasma cell proliferative disorder. Tissue deposits in light chain deposition disease are granular not fibrillar, and do not stain with Congo Red. The coexistence of SS and light chain depositon disease is unusual.